Analysis of the Impact of Polycystic Ovarian Syndrome on the Reproductive Health of Married Women in Tamil Nadu - Mrs. A. PONMALAR,; Dr. S .VASUKI, (The Bioscan, 2026)
Polycystic Ovarian Syndrome (PCOS) is a frequently occurring endocrine condition among women of reproductive age and a primary contributor to subfertility associated with anovulation. Moreover, insufficient awareness of PCOS, its management, and essential lifestyle modifications adversely affects clinical outcomes. This qualitative study explores women’s understanding and perceptions of the syndrome, its treatment options, and the lifestyle changes required for effective management. A total of 120 individuals with PCOS were selected through purposive sampling from Vriddhachalam, and telephonic interviews were also conducted. The themes derived from the analysis encompassed women’s understanding of PCOS; its causes, complications, and risk factors; treatment-related perceptions; and the perceived significance of health-promoting behaviors such as physical activity, sleep habits, and societal support. The respondents further emphasized the importance of nutrition, regular physical activity, and a wellness-oriented lifestyle. While medications assisted participants in achieving consistent menstrual cycles, they also produced side effects, which are discussed in the subsequent section. A small number of respondents reported being unaware of PCOS at the time of their diagnosis during adolescence. Overall, this study enhances the understanding of PCOS from a qualitative perspective that incorporates cultural context alongside relevant clinical and lifestyle considerations. Keywords Polycystic Ovarian Syndrome, Mensural Impact, Treatment, Life style changes.